"PrEP just isn't my priority": Adherence challenges among women who inject drugs participating in a pre-exposure prophylaxis (PrEP) demonstration project in Philadelphia, PA USA. (April 2021) - Felsher, Marisa; Ziegler, Eliza; Amico, K. Rivet; Carrico, Adam; Coleman, Jennie; Roth, Alexis M.
Abstract: Pre-exposure prophylaxis (PrEP) has the ability to curb HIV transmission among women if they are highly adherent (e.g. 6/7 weekly doses). In a recent PrEP demonstration project with 95 women who inject drugs (WWID) in Philadelphia, PA, USA, PrEP uptake was high but adherence was low. This qualitative study draws upon the Behavioral Model for Vulnerable Populations (BMVP) to describe how the context of 23 WWID's lives challenged PrEP adherence using narrative data from in-depth interviews. Content analysis suggests that women's need to organize their day around predisposing survival needs made it difficult to prioritize PrEP. Adherence was further challenged by dis-enabling structural forces such as entry into institutions that do not provide PrEP (e.g., drug treatment and correctional facilities) and medication diversion to illicit marketplaces. Overtime, women's perceived need for PrEP was dynamic: in periods they characterized as risky, women considered PrEP highly beneficial and described enhanced motivation to adhere. In periods of low perceived risk, women were less committed to continuing daily PrEP in the context of their competing survival needs. In sum, WWID faced challenges to PrEP adherence that correspond to all of the BMVP domains. To optimize PrEP for WWID, multi-level programs are needed that address the determinants that both increase HIV susceptibility and undermine adherence. Highlights: Poverty and homelessness made it difficult for women to prioritize daily PrEP use. Predatory pharmacies facilitated PrEP medication diversion. Criminal justice and drug treatment policies challenged PrEP continuation. Fluctuations in perceived HIV risk impacted perceived need for PrEP.